Big Data, Knowledge Mapping for Sustainable Development: A Water Quality Index Case Study - Lei Zhang (Emerging Science Journal, 2019)
Water quality assessment is an increasingly important area in environmental study. Assessment of water quality can be a process include multiple factors which can causing influence on water quality. Researchers have developed many evaluation indices In order to display the results of water quality evaluation more intuitively. Water quality index has been the important fields in sustainable water quality management. This research based on the papers published of 20 years from web of science, analyzed the data by using CiteSpace 5.0. The result shows the direction, frontiers and hotspots of water quality index. Research from institutes, research keywords, word frequency, quoted literature and Subjects. The result shows in view of the world, India, China, US, Brazil and Iran are major countries. From the hotspots and frontiers of research, key words such like water quality management, drinking water quality are the main research hotspots and frontiers of social network in the contamination of water and water quality problem in China and India. this study  provide a  method for scientists to keep up with the situation of the study on water quality management., and puts forward suggestions for the further research on sustainable water quality index.